Design of hydraulic lift system of technical equipment working in amusement industry - Miroslav Blatnický; Ján Dižo; Alyona Lovska; Vadym Ishchuk (Acta Technica Jaurinensis)
This paper examines the design and application of a telescopic hydraulic system for amusement industry equipment that experiences cyclic passenger loads. The system comprises three hydraulic cylinders, each with different diameters, which activate at various points as the device moves. To achieve static balance and lift the main beam from a horizontal to a vertical position, the forces exerted by the cylinders were calculated using static equilibrium equations. The system's design, including the length and angle of each cylinder, was based on the technical specifications of the equipment. Analytical and numerical methods were used to ensure the correct sizing of the cylinders and the system's overall effectiveness, resulting in a structure that operates safely and efficiently.